2018
DOI: 10.1093/omcr/omy090
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced cystic brain necrosis developing 10 years after linac-based stereotactic radiosurgery for brain metastasis

Abstract: Cystic brain necrosis (CBN) is a rare form of BN. It typically occurs as a very late complication, and no standard treatment has been established. We report a case of a 59-year-old man who developed CBN 10 years after radiation therapy for metastatic brain tumors. The therapy consisted of whole brain radiotherapy followed by linac-based stereotactic radiosurgery as a boost. Initially, the CBN continued to expand despite treatment with corticosteroids and bevacizumab. Therefore, we resected the tumor and implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The uses of radiosurgery in treating epilepsy, functional motor, and behavioral disorders are limited to a small number of centers globally. The radiosurgical treatment of lesions requires a source of high energy rays and a method of accurately applying the radiation, conforming to the target volume and preserving the surrounding tissue[27,28].…”
Section: Resultsmentioning
confidence: 99%
“…The uses of radiosurgery in treating epilepsy, functional motor, and behavioral disorders are limited to a small number of centers globally. The radiosurgical treatment of lesions requires a source of high energy rays and a method of accurately applying the radiation, conforming to the target volume and preserving the surrounding tissue[27,28].…”
Section: Resultsmentioning
confidence: 99%
“…No recurrence of cyst formation occurred in these two cases. Aizawa et al reported that cyst formation occurred 10 years after initial SRS [ 32 ]. In the long-term survivors treated with SRS/fSRT, even though follow-up MRI revealed no new brain metastasis and no recurrence, physicians should pay more attention to the development of cyst formation >10 years after SRS/fSRT.…”
Section: Discussionmentioning
confidence: 99%
“…In the long-term survivors treated with SRS/fSRT, even though follow-up MRI revealed no new brain metastasis and no recurrence, physicians should pay more attention to the development of cyst formation >10 years after SRS/fSRT. Cyst formation after SRS or SRT is summarized in Table 4 [ 10 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the understanding of the pathophysiology of RBN and the development of new drugs, some scholars have attempted to use new interventions for treat RBN (such as bevacizumab, nerve growth factor and gangliosides). The treatment results in recent years are summarized in Table 2 [5,62,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]. We summarize various treatment methods and related mechanisms involved in Figure 2.…”
Section: Treatmentmentioning
confidence: 99%